Analysis of Morbidity Rate, Handling, and Mitigation of Lumpy Skin Disease (LSD) in Cirebon Regency - Retno Widyani; Fitri Dian Perwitasari; Lilis Wahyuni (Jurnal Agrosci, 2026)
Background. Lumpy Skin Disease (LSD) is a strategic infectious animal disease that has a significant impact on the health of cattle and economic losses for farmers. Cirebon Regency has been one of the areas affected by the LSD outbreak since the beginning of 2023. Aims. This study aims to analyze the morbidity rate, form of treatment, and mitigation strategies of LSD disease in Cirebon Regency. Method. The research method used is a descriptive approach with quantitative and qualitative components (mixed methods). Quantitative data were obtained from LSD case reports in the iSIKHNAS system for the 2023–2025 period to calculate morbidity rates, while qualitative data were collected through interviews with farmers, animal health workers, and the Department of Agriculture related to LSD handling and mitigation. Results. The results of the study show that the LSD morbidity rate in Cirebon Regency has decreased significantly from 7.86% in 2023 to 0.23% in 2024, and slightly increased to 0.75% in 2025. The decrease in morbidity is related to increased control efforts, especially vaccination, handling sick livestock, and the active involvement of animal health workers. LSD management is carried out through supportive therapy, isolation of sick livestock, cage sanitation, and vector control, while mitigation is focused on vaccination, livestock traffic restrictions, biosecurity, and livestock education. The FMEA analysis shows that livestock traffic control, vaccination coverage, and vector control are the top priorities for mitigation, with the highest risk. Conclusion. This study concludes that LSD control in Cirebon Regency has shown positive results, but it is necessary to strengthen mitigation in an integrated and sustainable manner to prevent the re-emergence of LSD disease in the future. Implications. The policy implications of this study emphasize the need for an integrated, data-driven, and sustainable LSD control strategy. Synergy between local governments, animal health workers, and breeders is a key factor in reducing the risk of LSD transmission and minimizing the economic impact and health of livestock in Cirebon Regency.